The Effect of Store Atmosphere on the Decision to Stay with Purchase Interest as a Mediation Variable - Junhien, Hendra; Maisirata, Pasifikus (Manunggal Halim Jaya, 2026)
High purchase intention has been shown to influence guests' decision to stay at a hotel significantly. This study analyses the influence of store atmosphere on the decision to stay, with guest purchase intention as a mediating variable. This study used a quantitative approach, involving 172 respondents who were guests of the Borneo Hotel in Pontianak. The sample was selected through purposive sampling, with the criteria that respondents be guests who had stayed at least 1 night, be aged 18 or older, and be willing to participate voluntarily in the research process. In addition, data analysis was conducted using Structural Equation Modelling (SEM) techniques using AMOS software version 23 to achieve more precise and reliable research results. The results show that store atmosphere significantly influences guests' decision to stay. A hotel atmosphere that is perceived as attractive and comfortable, and that provides a pleasant experience, is an essential factor in increasing guest interest. Furthermore, purchase intention also plays a vital role in strengthening guests' tendency to stay. This study also shows that purchase intention acts as a mediating factor, increasing the relationship between store atmosphere and the decision to stay. Overall, this study confirms that the quality of a store's ambience not only directly influences the decision to stay, but the effect is even more pronounced when guests have high purchase intentions. These findings have important implications for hotels, encouraging them to continually improve the quality of their physical environments and ambience to attract guests and encourage them to stay.